Probing molecular environment through photoemission delays - Biswas, Shubhadeep; Foerg, Benjamin; Ortmann, Lisa; Schoetz, Johannes; Schweinberger, Wolfgang; Zimmermann, Tomas; Pi, Liangwen; Baykusheva, Denitsa; Masood, Hafiz A.; Liontos, Ioannis; Kamal, Amgad M.; Kling, Nora G.; et al. (Nature Physics, 2020)
Attosecond chronoscopy has revealed small but measurable delays in photoionization, characterized by the ejection of an electron on absorption of a single photon. Ionization-delay measurements in atomic targets provide a wealth of information about the timing of the photoelectric effect, resonances, electron correlations and transport. However, extending this approach to molecules presents challenges, such as identifying the correct ionization channels and the effect of the anisotropic molecular landscape on the measured delays. Here, we measure ionization delays from ethyl iodide around a giant dipole resonance. By using the theoretical value for the iodine atom as a reference, we disentangle the contribution from the functional ethyl group, which is responsible for the characteristic chemical reactivity of a molecule. We find a substantial additional delay caused by the presence of a functional group, which encodes the effect of the molecular potential on the departing electron. Such information is inaccessible to the conventional approach of measuring photoionization cross-sections. The results establish ionization-delay measurements as a valuable tool in investigating the electronic properties of molecules.
CRIS-Team Scopus Importer:2023-04-20